Privacy intrusion: Reasons and consequences - Meshram, Shruti (International journal of health sciences, 2022)
Given the dynamic nature of the online sphere, means of privacy intrusion and issues are changing rapidly. The literature review provides insight into the entities affected such as individuals, organizations, and Governments. An exploratory study is being conducted to discuss the current scenario for various privacy intrusion mechanisms, relevant regulations, and their severe effects on individuals. The tales of privacy intrusion generates privacy concerns among individuals and demand privacy protection policies and regulations by the Government. The study evolutes around a deep understanding of the reasons for privacy intrusion, its' current scenario, and its consequences for the same. The perception of misuse of technology is severely felt by the entity suffering individuals. Policymakers should heed attention to the factors which are invisible to logic and reasoning but have an insidious impact on individuals, groups, and society (Dinev et al., 2015). Privacy study is helpful for sociologists, psychologists, scholars of communications, management, information, organizational behavior, law and regulation, and public policy. The study also helps to build the judicial framework for the preparation of concurrent relevant privacy policies.